Evaluating the Antioxidant Potential and High Performance Thin Layer Chromatography Profiling of Siddha Formulation Veppampoo Mathirai - Chitra, S M; Anbu, N (Medical Science: Trends and Innovations Vol. 7, 2025)
In today’s world, herbals play a significant role in boosting immunity and preventing diseases. In some parts of the world, they are the primary required materials for healthcare system. In herbal formulation, some plants or specific combinations of herbs may act as antioxidants by exerting superoxide scavenging activity or by increasing superoxide dismutase activity in various tissue sites. Plant antioxidants play a vital role in the battle against cellular damage and disease. The present study aimed to study the antioxidant potential and basic TLC, HPTLC fingerprinting profile of poly herbal Siddha formulation Veppampoo Mathirai used for hypertension to regulate blood pressure in the Siddha system of medicine. The antioxidant action was measured by ABTS free radical scavenging assay, lipid peroxidation and nitric oxide scavenging measure. The common modern techniques that help to evaluate the quality control of complex herbal medicine are thin layer chromatography (TLC) and High performance thin layer chromatography (HPTLC). World Health Organization also indicated the above as a valuable tool to ensure the quality of medicinal plant products. Analysis of TLC was done by silica gel 60F254, 7X6 cm (Merck) and HPTLC by CAMAG Twin trough chambers. All outcomes of the sample were communicated as mean ± standard deviation compared with control. The study revealed the presence of a prominent peak at 366 nm in TLC analysis and twelve prominent peaks in HPTLC analysis with Retention factor (Rf) value ranging from 0.02 to 0.86. ABTS scavenging assay, lipid peroxidation and nitric oxide scavenging showed EC50 values of aqueous extract of Veppampoo mathirai at 55.32 \(μ\)g/mL, 51.3 \(μ\)g/mL and 51.31 \(μ\)g/mL, separately. The above results revealed that the aqueous extract of Veppampoo mathirai has solid antioxidant possibilities and is also a good source of natural antioxidants. It is concluded that Siddha formulation Veppampoo mathirai is a good source of natural antioxidants that can be utilized for age-related diseases like blood pressure as therapeutic.